Competencias básicas en matemáticas, de los estudiantes que ingresan a todos los programas académicos de la universidad católica popular del Risaralda (2021)
This current paper describes the level of the basic mathematics competences concerning to the numerical and variational thought and problem solving, from first semester students registered in the difference academic programs offered at Universidad Católica Popular del Risaralda between the 2005 and 2006 semesters, besides, the students obtained changes during the semester were analysed by checking the mathematics outcomes of the students first mid-term and final examination scores in each semester where the investigation was held, based on the development of the mathematics basic competencies a student must have when finishing high school, according to the curriculum guidelines established by the National Ministry of Education when it comes to mathematics Academic Area, standards proposal and competencies assessment.